2012
DOI: 10.1002/cm.21017
|View full text |Cite
|
Sign up to set email alerts
|

A review of models of fluctuating protrusion and retraction patterns at the leading edge of motile cells

Abstract: A characteristic feature of motile cells as they undergo a change in motile behavior is the development of fluctuating exploratory motions of the leading edge, driven by actin polymerization. We review quantitative models of these protrusion and retraction phenomena. Theoretical studies have been motivated by advances in experimental and computational methods that allow controlled perturbations, single molecule imaging, and analysis of spatiotemporal correlations in microscopic images. To explain oscillations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 107 publications
(175 reference statements)
1
59
0
Order By: Relevance
“…Similar propagating waves or evidence for excitability of signal transduction and cytoskeletal events have been observed in neutrophils (Weiner et al, 2007), mast cells (Wu et al, 2013), fibroblast (Ryan et al, 2012; Case and Waterman, 2011) and other cells (Winans et al, 2016). In some cases, the similar phase relationships among various components has been documented.…”
Section: The Signal Transduction “Excitable” Network or Stensupporting
confidence: 67%
“…Similar propagating waves or evidence for excitability of signal transduction and cytoskeletal events have been observed in neutrophils (Weiner et al, 2007), mast cells (Wu et al, 2013), fibroblast (Ryan et al, 2012; Case and Waterman, 2011) and other cells (Winans et al, 2016). In some cases, the similar phase relationships among various components has been documented.…”
Section: The Signal Transduction “Excitable” Network or Stensupporting
confidence: 67%
“…One natural choice would be to develop a more detailed description of the statistics of cell protrusions in neural crest, e.g. including stochastic protrusion and retraction [63] as has been modeled for Dictyostelium [64, 65]. Inclusion of hydrodynamic flow within the cells, as we have previously studied for single cells [31, 41], could potentially be relevant as well, especially if we were to extend our study from collisions in micropatterns to microchannels [66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that inhibitors of actin polymerization block their generation and migration (Ruthel and Banker, 1998;Toriyama et al, 2006;Weiner et al, 2007;Bretschneider et al, 2009). However, how actin polymerization mediates the wave-like migration of actin and associated proteins is unknown (Carlsson, 2010a;Ryan et al, 2012;Allard and Mogilner, 2013).…”
Section: Introductionmentioning
confidence: 99%